2017
DOI: 10.1017/s0007114517001891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary DHA:EPA ratios on gonadal steroidogenesis in the marine teleost, tongue sole (Cynoglossus semilaevis)

Abstract: The present study was conducted to investigate the effects of dietary DHA and EPA on gonadal steroidogenesis in mature females and males, with a feeding trial on tongue sole, a typical marine teleost with sexual dimorphism. Three experimental diets differing basically in DHA:EPA ratio, that is, 0·68 (diet D:E-0·68), 1·09 (D:E-1·09) and 2·05 (D:E-2·05), were randomly assigned to nine tanks of 3-year-old tongue sole (ten females and fifteen males in each tank). The feeding trail lasted for 90 d before and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Moreover, compared to total DHA+EPA contents, the effects of DHA/EPA ratio were interesting as well but relatively less studied (Sargent et al, 1999; Kim et al, 2002; Lee et al, 2003; Wu et al, 2003; Skalli and Robin, 2004; Hamre and Harboe, 2008; Wilson, 2009; Lund and Steenfeldt, 2011; ØStbye et al, 2011; Tocher, 2015). Our previous studies with marine species such as large yellow croaker Larmichthys crocea (Zuo et al, 2012a), Japanese seabass Lateolabrax japonicus (Xu et al, 2016) and tongue sole (Xu et al, 2017) have shown the significantly different roles of DHA and EPA in some physiological processes such as non-specific immune response and gonadal steroidogenesis. In the present study, taking advantage of completely sequenced genome data on tongue sole C. semilaevis , a genome-wide hepatic transcriptome analysis was conducted with tongue sole following an 80-day feeding trial with diets containing different DHA/EPA ratios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, compared to total DHA+EPA contents, the effects of DHA/EPA ratio were interesting as well but relatively less studied (Sargent et al, 1999; Kim et al, 2002; Lee et al, 2003; Wu et al, 2003; Skalli and Robin, 2004; Hamre and Harboe, 2008; Wilson, 2009; Lund and Steenfeldt, 2011; ØStbye et al, 2011; Tocher, 2015). Our previous studies with marine species such as large yellow croaker Larmichthys crocea (Zuo et al, 2012a), Japanese seabass Lateolabrax japonicus (Xu et al, 2016) and tongue sole (Xu et al, 2017) have shown the significantly different roles of DHA and EPA in some physiological processes such as non-specific immune response and gonadal steroidogenesis. In the present study, taking advantage of completely sequenced genome data on tongue sole C. semilaevis , a genome-wide hepatic transcriptome analysis was conducted with tongue sole following an 80-day feeding trial with diets containing different DHA/EPA ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies on lncRNAs in fish have been restricted to model fish species, and most of the studies focused on developmental biology (Kaushik et al, 2013; Liu et al, 2013; Haque et al, 2014; Dhiman et al, 2015; Al-Tobasei et al, 2016; Wang et al, 2016, 2017; Sarangdhar et al, 2017; Hu et al, 2018). Therefore, following our previous studies on lipid/fatty acid nutrition of marine fish (Zuo et al, 2012a,b; Xu et al, 2016, 2017), the present study was aimed at investigating the potential involvement of lncRNAs in effects of dietary fatty acids on a non-model marine teleost tongue sole Cynoglossus semilaevis , which is also an important aquaculture species. A feeding trial was conducted in this study, followed by hepatic transcriptome analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tongue sole, fatty acids have been proven to be required for gonadal steroidogenesis. An appropriate DHA:EPA ratio can induce high expression of the follicle-stimulating hormone receptor (FSHR), steroidogenic acute regulatory protein (STAR), 17α-hydroxylase (P450c17) and 3β-hydroxysteroid dehydrogenase (3β-HSD), which are involved in steroidogenesis ( Xu et al, 2017 ). Thus, the retinol metabolism and fatty acid metabolism pathways may be involved in oocyte maturation, including steroidogenesis and oocyte meiosis, in tongue sole.…”
Section: Discussionmentioning
confidence: 99%
“…2). Different dietary DHA:EPA ratio increased the star mRNA expression in tongue sole (Cynoglossus semilaevis) (Xu et al 2017). Cabas et al (2013), treated gilthead seabream with 17aethynylestradiol which decreased the mRNA expression of the star.…”
Section: Starmentioning
confidence: 99%